BUILD COMPUTER NETWORK USING TCP / IP VERSION 6 - Yudhi Irawan Chandra (Majalah SIKOMTEK, 2010)
This paper will explain about IP version 6 and how pengalokasiannya. This time to request an IP address that has been done through agencies appointed by the IANA (Internet Assigned Numbers Authority) which are determined by region, including the APNIC (Asia Pacific Network Information Center), which handles special requests IP address for the Asia Pacific region, including areas served by APNIC is Indonesian. Similar organizations that handle regions of North America, South America, the Caribbean, and Sub-Saharan Africa is ARIN, whereas in Europe, the Middle East, and parts of Africa RIPE-NCC is. Keywords: Computer Networks, Internet, TCP/IPV6